Amalan sumber manusia dan komitmen pekerja: peranan pengantaraan model AMO dalam kalangan PKS di Selangor - Elaina Rose Johar,; Nadzirah Rosli,; Norzanah Mat Nor,; Roshidi Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Employee commitment continues to be a major concern for small and medium enterprises (SMEs) in Malaysia. A decrease in SME productivity and frequent job turnover among employees contribute to a decrease in employee commitment. Over time, researchers have found ways to maximize the potential of different and distinctive human resources (HR) and ways to retain them. The purpose of this study is to analyze the relationship between rewards, recruitment, employee involvement, and employee commitment. This study also aims to provide empirical evidence based on theory that shows the role of the ability, motivation, and opportunity model (AMO) as a mediator in obtaining employee commitment and using Social Exchange Theory (SET) to verify the theoretical rationale of the study model. Data was collected from 211 employees working in small and medium enterprises (SMEs) in Selangor, Malaysia. Partial least squares-structural equation modeling (PLS-SEM) was used in this research study to test the developed hypotheses. PLS-SEM with bootstrapping estimation was used to predict and estimate the relationship between variables. The findings show that both rewards and employee involvement have significant effects on employee commitment, and the AMO MODEL mediates the relationship for both recruitment and employee involvement. Therefore, organizations especially SMEs should improve existing reward systems to ensure employees remain committed. Organizations should also be wise to choose employees according to their skills and abilities and provide opportunities for employee involvement in the organization's affairs and activities.